Challenges in managing a patient with central post stroke pain - Salim, Mazatulfazura Sf; Hanafi, Muhammad Hafiz; Tan, Yew Chin; Kassim, Nur Karyatee; Mazlan, Mazlina (Ibn Sina Trust, 2019)
Objective: This is a case illustration of the challenges in managing a patient with central post stroke pain secondary to right thalamic bleed. We describe in detail the events of this case management and the challenges that we had encountered. Method: We report a case of a 68-yearold lady who had right thalamic bleed secondary to hypertensive crisis in 2015 and was further complicated with central post stroke pain over the hemiparetic side. In our report, we describe in detail the challenges in managing the patient to improve her function to achieve a better quality of life. Conclusion: This article illustrates the importance of a multidisciplinary approach and knowledge of various methods in managing a patient with central post stroke pain.